Pinkalicious and the pinkettes ebook - Kann, Victoria (I Can Read, Level 1: Pinkalicious., 2020)
#1 New York Times bestselling author Victoria Kann brings young readers a Pinkalicious I Can Read adventure that celebrates creativity and resourcefulness! Rock out with Pinkalicious and her friends in this Level One I Can Read. Pinkalicious and her friends want to start a band, but they don't have any instruments! Pinkalicious will need to find a creative answer. When Pinkalicious realizes there are amazing sounds all around, she figures out what to do. Pinkalicious and the Pinkettes is a Level One I Can Read book, which means it's perfect for children learning to sound out words and sentences. Readers can watch Pinkalicious and Peterrific on the funtastic PBS Kids TV series Pinkalicious & Peterrific!